1973
DOI: 10.1017/s0021859600057993
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the effect of protein intake and stage of gestation on the proportion of urinary nitrogen excreted as urea in sheep

Abstract: The effect of altering the level of protein intake on urea excretion in ewes was assessed in two separate experiments.In Expt 1, 14 pregnant (during the last 20 days of gestation) and 10 non-pregnant ewes were each offered a different level of digested N intake in the range 5-25 g/day. At all levels of protein intake urea N excretion was lower in pregnant than in nonpregnant ewes.In Expt 2, 21 pregnant ewe lambs were each offered one of three diets supplying mean intakes of 83 (Tl), 113 (T2) or 147 (T3) g crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1974
1974
1979
1979

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…When the amount of urea fed to the 0-cows was increased, the total urinary and urea nitrogen contents increased, and also the proportion of urea nitrogen of the total nitrogen (Figures 1 and 2). Many scientists have found the same thing as regards cows on normal feeding, irrespective of whether the cows are pregnant, dry or milk-producing (Livingston et al 1962, Kertz 1970, Robinson et al 1973, Paque et al 1973). Kertz has observed that the total urinary and urea nitrogen are influenced both by nitrogen intake and nitrogen requirement.…”
Section: Discussionmentioning
confidence: 93%
“…When the amount of urea fed to the 0-cows was increased, the total urinary and urea nitrogen contents increased, and also the proportion of urea nitrogen of the total nitrogen (Figures 1 and 2). Many scientists have found the same thing as regards cows on normal feeding, irrespective of whether the cows are pregnant, dry or milk-producing (Livingston et al 1962, Kertz 1970, Robinson et al 1973, Paque et al 1973). Kertz has observed that the total urinary and urea nitrogen are influenced both by nitrogen intake and nitrogen requirement.…”
Section: Discussionmentioning
confidence: 93%
“…An increase in the ratio of urea nitrogen to total excreted nitrogen with increasing dietary protein would appear to be the cause of the differences in urine energy-nitrogen ratios discussed above. Though evidence of such an increase in pigs is lacking, Robinson, Scott & Fraser (1973) showed that in pregnant and nonpregnant ewes the urea nitrogen to total nitrogen ratio in urine did increase as the daily allowance of dietary protein was increased.…”
Section: Discussionmentioning
confidence: 99%
“…inhibition of glycine synthase by branched-chain ¡x-ketoacids originating from muscular proteolysis is a possible mechanism for glycine accumulation (O'Brien, 1978). The reduction in urea excretion during late pregnancy (Robinson, Scott and Fraser, 1973) may arise from a smaller release of amino acids from maternal tissues or an increased storage, a higher uptake of amino acids by the foetus, or an enhanced urea recycling to the rumen (Nolan and Leng, 1970). This last mechanism could account for the positive effect on nitrogen retention of an increase in metabolizable energy intake (Guada, Robinson and Fraser, 1975).…”
Section: Introductionmentioning
confidence: 99%